Analisa Perbandingan Komposisi Agregat Halus Pasir Kuarsa dan Fly Ash pada Beton Geopolymer Berbasis Binder Kalium Hidroksida Terhadap Kuat Tekan dan Daya Serap Beton - Indah Rosanti; Rona Ariyansyah; Satriyo Utomo; Lelly Marini; Indah Permatasary; Mega Septiani Mega (Jurnal Poli-Teknologi, 2024)
The development of concrete construction has the impact of increasing cement production anddamaging the balance of nature because every 1kg of cement production produces CO2 emissionsof 0.5 - 0.7 kg. To reduce this iMPact, geopolymer concrete innovation was formed. Geopolymerconcrete is formed from the polymerization reaction of silica (Si) and alumina (Al) compoundsfound in quartz sand and fly ash waste from burning coal which has binding properties like cement.Fly ash reacts with alkaline activators of potassium hydroxide (KOH) and sodium silicate(Na2SiO3). The research method used is a quantitative method with experimental studies in thelaboratory. Geopolymer concrete mix design refers to previous research. Geopolymer concrete testobjects are cylindrical with a size of 100 x 200 mm. There are 2 variations of the composition ofalkali activator forming geopolymer concrete, namely 8M KOH concentration, alkali activatorratio of 1:1 mol ratio and 10M KOH, alkali activator ratio of 1:1.5 mol ratio. The composition offly ash and quartz sand for each binder was 20%:80%, 40%: 60%, 50% : 50%, 60% : 40%,80%:20% with a total of 36 samples. Testing compressive strength and absorption at the age of 14and 28 days. The results of the compressive strength obtained ≤ 50 MPa where the concrete doesnot include high quality concrete and not for the needs of precast construction. The results ofaverage concrete absorption reached 3,72%, which already met the permissible absorption of amaximum of 10%. Keywords: Fly Ash, Quartz Sand, Potassium Hydroxide, Geopolymer Concrete.